EbMYBP1, a R2R3-MYB transcription factor, promotes flavonoid biosynthesis in Erigeron breviscapus - Zhao, Yan; Zhang, Guanghui; Tang, Qingyan; Song, Wanling; Gao, Qingqing; Xiang, Guisheng; Li, Xia; Liu, Guanze; Fan, Wei; Li, Xiaoning; Yang, Shengchao; Zhai, Chenxi (Frontiers in Plant Science, 2022)
Erigeron breviscapus, a traditional Chinese medicinal plant, is enriched in flavonoids that are beneficial to human health. While we know that R2R3-MYB transcription factors (TFs) are crucial to flavonoid pathway, the transcriptional regulation of flavonoid biosynthesis in E.breviscapus has not been fully elucidated. Here, EbMYBP1, a R2R3-MYB transcription factor, was uncovered as a regulator involved in the regulation of flavonoid accumulation. Transcriptome and metabolome analysis revealed that a large group of genes related to flavonoid biosynthesis were significantly changed, accompanied by significantly increased concentrations of the flavonoid in EbMYBP1-OE transgenic tobacco compared with the wild-type (WT). In vitro and in vivo investigations showed that EbMYBP1 participated in flavonoid biosynthesis, acting as a nucleus-localized transcriptional activator and activating the transcription of flavonoid-associated genes like FLS, F3H, CHS and CHI by directly binding to their promoters. Collectively, these new findings are advancing our understanding of the transcriptional regulation that modulates the flavonoid biosynthesis.